Clinical manifestations comparison in hospitalized pregnant and non-pregnant women with Covid-19 at Mataram University Hospital, Mataram, Indonesia - Putu Diah Ananda Putri Atmaja; Ario Danianto; Titi Pambudi Karuniawaty (Universitas Airlangga, 2022)
HIGHLIGHTS 1. Clinical manifestations in pregnant and non-pregnant women with Covid-19 were identified. 2. Pregnant women with Covid-19 mostly had asymptomatic clinical manifestations, while non-pregnant women with Covid-19 mostly had symptomatic clinical manifestations. 3. Recognition of the clinical manifestations in pregnant women with Covid-19 may help early detection and treatment of pregnant Covid-19 patients.   ABSTRACT Objectives: To know a comparison of clinical manifestations in pregnant and non-pregnant Covid-19 patients who are hospitalized at Mataram University Hospital. Materials and Methods: This study was a descriptive observational study with a cross-sectional approach, using secondary data in the form of medical records. This study uses a total sampling technique, sample selection based on affordable population, inclusion criteria, and exclusion criteria. The data was processed with SPSS 25th version and analyzed with a Chi-square analysis test. Results: In this study, it was found that 145 women confirmed Covid-19 on RT-PCR, 89 of which were pregnant and 56 others weren't; 85.4% of the included pregnant women were in the 3rd trimester. Clinical manifestations in pregnant women are 73.0% asymptomatic while symptomatic in 60.7% of the non-pregnant women. In symptomatic pregnant women, most common clinical symptoms were nausea, vomiting, cough, and headache; while the most common clinical symptoms in non-pregnant women were cough, anosmia, and headache. Chi-square analysis test showed a significant relationship with p = 0.000 (p < 0.05) in clinical manifestation comparison. Conclusion: There are differences in clinical manifestations in pregnant and non-pregnant women with Covid-19. The most common clinical manifestation in pregnant women was asymptomatic and in non-pregnant women the most common clinical manifestation was symptomatic.